2009
DOI: 10.1136/hrt.2009.174268
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for continuous chest compression cardiopulmonary resuscitation

Abstract: Every year more than a million cardiac arrests are documented in the industrialised nations of the world, with the majority occurring in settings outside hospital. A major factor in survival after out-of-hospital cardiac arrest (OHCA) is early institution of bystander resuscitation efforts. Sadly, the majority of OHCAs do not receive bystander resuscitation for a variety of reasons. One of them is the requirement for mouth-to-mouth (MTM) ventilation. The 2008 American Heart Association recommendation for "hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 68 publications
(71 reference statements)
0
12
0
2
Order By: Relevance
“…6 Studies have reported initiation of BCPR can increase survival by three-folds and early BCPR initiated less than 4 min after cardiac arrest can increase the odds of survival by 4.5 times. 7 Previous evidence suggested a significant regional variation in the incidence of OHCA events in Singapore. 8 One local study reported significantly poor survival outcomes among residential OHCA cases.…”
Section: Introductionmentioning
confidence: 99%
“…6 Studies have reported initiation of BCPR can increase survival by three-folds and early BCPR initiated less than 4 min after cardiac arrest can increase the odds of survival by 4.5 times. 7 Previous evidence suggested a significant regional variation in the incidence of OHCA events in Singapore. 8 One local study reported significantly poor survival outcomes among residential OHCA cases.…”
Section: Introductionmentioning
confidence: 99%
“…En los Estados Unidos de América, el Consejo de Acreditación de la Educación Médica de Grado considera a la reanimación cardiopulmonar como una de las habilidades generales que todos los egresados de escuelas de medicina deben poseer (9).…”
Section: Discussionunclassified
“…En Estados Unidos la Accreditation Council for Graduate Medical Education -ACGME definió la RCP como una de las competencias genéricas de los egresados de Medicina 14 . En nuestro país, la enseñanza de RCP es parte de la malla curricular de las principales Escuelas de Medicina.…”
Section: Discussionunclassified